ZIKIR SEBAGAI MEDIA KOMUNIKASI - Muthiah Ahmad (Jurnal Dakwah Tabligh, 2015)
The emergence of various assemblies’ dhikr trying to provide solutions for the pilgrims who were experiencing inner restlessness and spiritual aridity. It has become a common phenomenon that the modern century marked by development science and technology, encourage positive change at the same time adversely affect human life. One negative aspect is the loss of balance and peace of the human soul. Not a few people who were facing inner restlessness until almost could lead to frustration in his life. Recitation is also a form of communication to God to do in those conditions and under any circumstances, because the remembrance was to remember, feel, see the omnipotence of God, in the Encyclopedia of Islam which explains that the term of remembrance has multi understanding them is to call, said, remember, keep, or understand something good. One of the means to be able to communicate with God is by way of remembrance, which would take a person surrendered to Allah. With syariah the slave can communicate with his Creator. Allah is the communicant, His is the communicator and the remembrance is medium.